2021
DOI: 10.1093/plcell/koab100
|View full text |Cite
|
Sign up to set email alerts
|

Rare instances of haploid inducer DNA in potato dihaploids and ploidy-dependent genome instability

Abstract: In cultivated tetraploid potato (Solanum tuberosum), reduction to diploidy (dihaploidy) allows for hybridization to diploids and introgression breeding and may facilitate the production of inbreds. Pollination with haploid inducers yields maternal dihaploids, as well as triploid and tetraploid hybrids. Dihaploids may result from parthenogenesis, entailing the development of embryos from unfertilized eggs, or genome elimination, entailing missegregation and the loss of paternal chromosomes. A sign of genome eli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Potentially, formation of telomeres may also stabilize certain centromeric fragments. Instability is commonly associated with haploid induction (Maheshwari et al 2015;Tan et al 2015;Kuppu et al 2015;Amundson et al 2021;Sun et al 2022) and with wide crosses (Madlung et al 2005;Shibata et al 2013), and minis are likely to arise in these crosses (Seymour et al 2012;Tan et al 2015;Kuppu et al 2015). One question is whether minichromosomes require mutations in specialized loci of DNA metabolism for their formation and maintenance.…”
Section: Minis From Genomic Instabilitymentioning
confidence: 99%
“…Potentially, formation of telomeres may also stabilize certain centromeric fragments. Instability is commonly associated with haploid induction (Maheshwari et al 2015;Tan et al 2015;Kuppu et al 2015;Amundson et al 2021;Sun et al 2022) and with wide crosses (Madlung et al 2005;Shibata et al 2013), and minis are likely to arise in these crosses (Seymour et al 2012;Tan et al 2015;Kuppu et al 2015). One question is whether minichromosomes require mutations in specialized loci of DNA metabolism for their formation and maintenance.…”
Section: Minis From Genomic Instabilitymentioning
confidence: 99%
“…Abnormal dihaploids were also noted (1.4% for PL-4, 10.1% and 6.3% for IvP101 and IvP35, respectively). These could represent extreme aneuploidy cases (Tan et al 2015;Amundson et al 2021).…”
Section: Haploid Inductionmentioning
confidence: 99%
“…Three hypotheses have been proposed for the mechanism of haploid induction in potatoes: parthenogenesis, parentspecific chromosome elimination and egg-pseudo fertilization (Wangenheim et al 1960;Clulow et al 1991;Amundson et al 2021). The exact mechanism at play has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…We asked if the method could be useful in eight comparable, but unrelated dihaploid families generated through haploid induction crosses. Seven of these dihaploid families (Amundson et al 2020b) revealed the presence of translocated or misplaced heterochromatic and pericentromeric blocks, but no arm translocations (Suppl. Fig.…”
Section: Analysis Of Additional Dihaploid Families Of Potatomentioning
confidence: 99%